Translation Of Chinese Political Discourse For International Communication: A Diplomatic Narrative Account - Xu, Dong (2024)
The increasing global engagement and rising comprehensive national strength of China have heightened international interest in the country, emphasising the importance of constructing China’s international image. Key to this is the translation of Chinese political discourse, which plays an essential role in international communication and in portraying China’s narrative and culture. Central to this context is the book Xi Jinping: The Governance of China, reflecting the ideologies of socialism with Chinese characteristics in the new era and representing significant 21st-century Marxist literature and essential Chinese political discourse. The objectives of this study are to identify the core narrative features in political discourse translation, describe framing strategies in the translation, specify translation methods used by translators, and analyse the narrative paradigm in assessing Chinese political discourse translation. Baker’s (2018) narrative theory supports this research, highlighting the translator’s active role in constructing narratives that not only reflect but also shape reality. Using Xi Jinping: The Governance of China as the corpus, this study applies textual analysis from a narrative theory perspective. The findings reveal that integrating narrative theory with political discourse translation enriches the field of narratology and provides new theoretical insights and methodologies for political discourse translation research. This approach offers novel pathways for achieving effective translation missions.